Utilization of Fly Ash as a Coagulant in the Coagulation Process of Coal Yard Wastewater - Fajri Wan Hidayat; Ramadhani, Arnesya; Ichya Musytafizur Ziqri; Siti Khuzaimah (University of Jember, 2026)
Coal yard wastewater is an industrial effluent characterized by high turbidity, high total suspended solids (TSS), and acidic pH, which may cause environmental pollution if discharged without proper treatment. One commonly applied treatment method is coagulation; however, the use of conventional chemical coagulants may increase operational costs and sludge generation. This study aims to evaluate the use of fly ash as an alternative coagulant for treating coal yard wastewater. Fly ash was activated using sulfuric acid (H2SO4) at concentrations of 1%, 3%, 5%, 7%, 10%, and 15%. The coagulation process was conducted using coagulant dosages of 2 mL and 4 mL per 500 mL of wastewater. The analyzed parameters included pH, turbidity, and total suspended solids (TSS). The results showed that activated fly ash significantly reduced turbidity and TSS by up to approximately 80%. The optimum performance was achieved at fly ash activation concentrations of 5% and 7%. These results indicate that fly ash has strong potential as an effective, economical, and environmentally friendly alternative coagulant for coal yard wastewater treatment.